Distribution and composition of butterfly species along the latitudinal and habitat gradients of the Western Ghats of India - Anand Padhye; Sheetal Shelke; Neelesh Dahanukar (Check List, 2012)
Distribution of butterfly species along the latitudinal and habitat gradients of the Western Ghats was studied. The Western Ghats was divided into 14 latitude zones and the species diversity in each latitude zone, along with habitats of their occurrence, were studied using the data from literature survey for the entire Western Ghats as well as data from personal observations in the areas between 14°N to 20°N latitudes. Out of 334 species recorded from the Western Ghats, 58 species were found in all latitudinal zones, while 5 species were reported in only one latitudinal zone. Further, southern Western Ghats consisted of more number of species and more number of genera as compared to northern Western Ghats. Latitudinal zones between 10°N to 12°N had most of the Western Ghats endemic species. Habitat wise distribution of species revealed three significant clusters grossly separated by the level of human disturbance. Evergreen forest habitats supported maximum number of species endemic to the Western Ghats.